Pop Culture, Commercialisation of Indigenous Music, and the Urhobo GEN-Z Audience in Nigeria - OKPEKI, Philo Igue (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This study examines the commercialization of indigenous music and the reaction of Urhobo Gen-Z audience in Nigeria. It assesses the role of Gen-Z in the commercialization of indigenous Urhobo music. In other words, the research argues that the Gen-Z generation has impacted tremendously on the landscape of indigenous music in Urhobo land in Delta State, Nigeria. Gen-Z is the short form for generation-Z. This group of young adults were born from the mid-1990s to the early 2010s. The study employs the qualitative methodology and uses interview as a tool to complement the qualitative method. The research is anchored on Adam Smith’s (1776) theory of commercialization. Findings in this study reveal that the reaction of Gen-Z participants to the commercialization of indigenous music genre is relatively positive. Also, their consumption of indigenous Urhobo music is moderate compared to other Afrobeat music genres highly rated by Gen-Z in Nigeria. Gen-z has impacted on indigenous music of Urhobo in Nigeria due to high rate of streaming of traditional music on multimedia platforms like Spotify. The research concludes that, there is a positive reaction towards commercialization of indigenous music by Urhobo Gen-Z audience in Nigeria. The study recommends that the Gen-Z generation of the Urhobo cultural landscape should increase the rate of patronage of the Urhobo music, especially tracks infused with traditional rhythms, folk elements and popular contemporary genres.